2013
DOI: 10.1589/jpts.25.833
|View full text |Cite
|
Sign up to set email alerts
|

Surface EMG during the Push-up plus Exercise on a Stable Support or Swiss Ball: Scapular Stabilizer Muscle Exercise

Abstract: [Purpose] Scapular stabilizer strengthening exercise is crucial for shoulder rehabilitation. The purpose of this study was to compare two types of push-up plus exercises, on a stable and unstable bases of support, using surface electromyography (EMG), to suggest an effective shoulder rehabilitation program. [Subjects and Methods] Ten healthy men volunteered for this study. All volunteers performed two sets of push-up plus exercise (standard push up and knee push up) on stable and unstable bases of support. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 20 publications
0
42
1
2
Order By: Relevance
“…Previously, no studies have been conducted on differences in muscle activities due to a difference in support surface during the plank exercise. However, compared to a previous similar study that exhibited n difference in muscle activities of shoulders and trunk according to a state of support state during push-up exercise, the present study also showed a difference in muscle activities when instability of support surface on the floor was high (Seo et al, 2013). In the previous study, muscle activities around shoulders were significantly higher in an unstable support surface against arms than in a stable support surface statistically.…”
Section: ⅳ Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…Previously, no studies have been conducted on differences in muscle activities due to a difference in support surface during the plank exercise. However, compared to a previous similar study that exhibited n difference in muscle activities of shoulders and trunk according to a state of support state during push-up exercise, the present study also showed a difference in muscle activities when instability of support surface on the floor was high (Seo et al, 2013). In the previous study, muscle activities around shoulders were significantly higher in an unstable support surface against arms than in a stable support surface statistically.…”
Section: ⅳ Discussioncontrasting
confidence: 61%
“…Although a number of studies have been conducted on the plank as an exercise to increase muscle activities and muscle strength in abdomen, few studies have been conducted on muscles according to a support surface (Kim et al, 2016). Depending on the support surface of the floor, changes in muscle activities in trunk, arms, and legs were found during push-ups (Cho and Choi, 2016;Seo et al, 2013). Studies on the plank have been focused on strengthening abdominal muscles among trunk muscles (Tong et al, 2014).…”
Section: ⅰ Introductionmentioning
confidence: 99%
“…Twelve articles focused on the effects of the base of support during PUP exercises. 9,[15][16][17][18][19][20][21][22][23]51,52 After further checking for the meta-analysis, 1 article was excluded due to insufficient data for the means and standard deviations. 51 Therefore, 11 articles were included in this meta-analysis for analyzing the differences in SA and UT muscle activity during the PUP performed on stable and unstable surfaces.…”
Section: Study Selectionmentioning
confidence: 99%
“…[12][13][14] After finding that the standard PUP (SPP) and knee PUP exercises induced the highest SA and lowest UT : SA EMG measures, Ludewig et al 8 recommended these exercises for selective SA strengthening. Researchers 5,9,[15][16][17][18][19][20][21][22][23][24][25][26] have investigated whether the PUP exercise performed on different unstable bases stimulated mechanoreceptors and increased SA EMG activity, thereby enhancing shoulder-joint stabilization. The use of unstable or stable surfaces during the PUP exercise is under debate.…”
mentioning
confidence: 99%
“…48 Scapular stabilizers may be similar to postural support muscles where their function contributes toward maintaining normal shoulder kinematics and are integral for shoulder health and function; these muscles include the serratus anterior, 49,50 trapezius, 51 and latissimus dorsi. 52 However, there is no consensus on the behavior of these muscles in the presence of pain.…”
Section: Discussionmentioning
confidence: 99%